A unilateral tumor of the left wall of the maxillary sinus - a case study - Grzegorz Wróbel (Kazimierz Wielki University, 2018)
Neoplasms of the maxillo-facial area, including the sinuses paranasal, nasal, become an increasingly difficult challenge for contemporary oncology. Information on the frequency of occupation of the anatomic area is of great importance especially in the diagnosis of tumors infiltrating poorly available physical examination, because in these cases there is a greater risk of overlooking the disease at an early stage. Maxillary sinus tumors are rare cancers and commonly reported with nasal sinus cancers and other paranasal sinuses. A 68-year-old woman with visible lesions near the left cheek, in whom there was a limitation of the field of view due to the extensive nature of the pathological change. The tumor causes the features of the segmental destruction of the left nasal bone and segmentally destroys the anterior bone wall of the left maxillary sinus. Medical imaging is essential in diagnosing and assessing the severity of these cancers.